(untitled) (Applied Biological Research, 2015)
A field experiment was conducted at Regional Research Station Wadura, Sopore (Kashmir) during kharif 2013 to assess the impact of a phosphate solubilizing bacterium (PSB) Bacillus subtilis and vesicular arbuscular mycorrhiza (VAM) on maize cv. ‘KG-2’. The treatments comprised of 3 levels of biofertilizers (control, PSB and VAM) and 4 levels of inorganic phosphorus fertilizer [0, 25, 50 and 100% recommended dose of fertilizer (RDF) i.e. 60 kg P ha-1]. The experiment was laid out in a randomized complete block design with each treatment replicated thrice. Maximum plant height (166 cm), biomass production (104 q ha-1), grain yield (46.0 q ha-1) and crude protein (10%) were recorded in treatment VAM + PSB + 50% RDF. The use of VAM and PSB in combination with different P levels enhanced plant NPK uptake over control. Maximum uptake of N (103.0 kg ha-1), P (29.1 kg ha-1) and K (95.6 kg ha-1) was observed in treatment combination of VAM +PSB + 50% RDF.